PERAN KEJAKSAAN DAN PERAN JAKSA PENUNTUT UMUM DALAM PENEGAKAN HUKUM - SUMANTRI . (LP2MTBM MAKARIOZ, 2020)
The writing of this paper aims to find out the role of the prosecutors and the public prosecutor in law enforcement. The writing of this paper uses the literature review method (library research) based on expert opinions and research journals that support the topic of this paper. From the discussion it can be concluded that the actions taken by the public prosecutor in both the pre-prosecution and prosecution processes were actually carried out on the basis of justice and truth based on the Almighty God, Enforcement of justice for justice would of course also include fair for the accused, fair for the community affected by the actions of the accused and fair in the eyes of the law, so naturally what is done by the public prosecutor in the context of law enforcement is to achieve legal objectives namely legal certainty, bridging a sense of justice and the benefit of the law for justice seekers.